Soil moisture and its importance for tundra plants - Kemppinen, Julia (Helsingin yliopisto, 2020)
Water is fundamental for plant life, as it affects the growth, survival, and spatial patterns of vegetation. Here, I explored soil moisture and its ecosystem effects to answer: 1) What controls soil moisture variation? 2) How is water linked to vegetation? 3) Do plants influence water resources? I focused on the moisture of the top-soil layer (0 – 10 cm) in Fennoscandian mountain tundra. First, I evaluated environmental conditions controlling soil moisture variation. I used different modelling methods (generalized linear models, generalized additive models, generalized boosted regression models, and random forests) to account for the uncertainties related to each multivariate technique. On average, the model fit was R2 = 0.60 and the predictive performance R2 = 0.47. The spatial variation of soil moisture was most related to a topographic proxy of soil water accumulation and the depth of the organic soil layer. These results demonstrated that moisture can be modelled using topography and soil data. Secondly, I examined the influence of three water aspects (spatial and temporal variation of soil moisture, and fluvial disturbance) on vascular plants, mosses, and lichens. I used species distribution modelling, a framework for analysing the spatial patterns of species in relation to the environment. The species groups were most related to the spatial variation of soil moisture, albeit species had diverse responses. In general, water is not scarce in the tundra, yet the water aspects improved the models highlighting water as a multifaceted driver of the ecosystem. In addition, I investigated if plant-environment relationships were universal in the tundra. Here, I used hierarchical generalized additive models to compare sites across the hemispheres. I combined plant trait records with data on their environmental drivers. The local variation of conditions within the sites was overridden by global relationships indicating that these links are generalisable across the tundra sites. The results provide empirical evidence ...